Report of the preparatory meeting of African experts for the African ministerial conference on trade development and monetary problems Addis Ababa, 27-30 March 1973 (Abidjan : United Nations Economic Commission for Africa, 1973)
Report of the preparatory meeting of African experts for the African ministerial conference on trade development and monetary problems Addis Ababa, 27-30 March 1973
rpm 19/02/2019
Ref
Keywords: Trade Development; Monetary Problems; Addis Ababa